O financiamento da média e alta complexidade do SUS:uma análise dos recursos financeiros da terapia renal substitutiva - Pescuma Junior, Antonio (2013)
In this research will be an analysis about the problem of financing of SUS throughout its existence, with questions about Desvinculações das Receitas da União(DRU), and the current economic policy. We conducted a study about the financial progress of Fundo Nacional da Saúde (FNS) and Média e Alta Complexidade (MAC) before and after the term of Pacto pela Saúde. It was verified that the MAC block has a financial higher participation compared to other blocks of financing. Finally, it was found that Terapia Renal Substitutiva (TRS) concentrates the most part of the financial resources present in the MAC